2015
DOI: 10.1016/j.ajog.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Association between ovarian stimulators with or without intrauterine insemination, and assisted reproductive technologies on multiple births

Abstract: Although the risk of multiple births associated with invasive ART can be decreased by elective implementing of single embryo transfer, special attention should be paid to the greatly increased risk associated with ovarian stimulation used alone or with IUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The risk of monozygotic twinning is increased when culture is extended to the blastocyst stage, and in cleavage stage embryos with assisted hatching (62, 6673). A recent case-control study from Canada reported that the use of ovarian stimulators alone and with intrauterine insemination greatly increased the risk of multiple births (AORs of 4.5 and 9.32, respectively) (74). …”
Section: Discussionmentioning
confidence: 99%
“…The risk of monozygotic twinning is increased when culture is extended to the blastocyst stage, and in cleavage stage embryos with assisted hatching (62, 6673). A recent case-control study from Canada reported that the use of ovarian stimulators alone and with intrauterine insemination greatly increased the risk of multiple births (AORs of 4.5 and 9.32, respectively) (74). …”
Section: Discussionmentioning
confidence: 99%
“…This can serve as indicator for a similar trend among medically assisted reproduction nonparticipants, which minimize the occurrence of a selection bias. The differences in the education level and socioeconomic status, between participants and nonparticipants, may affect the generalizability of our results (Chaabane et al., ). Nevertheless, this has a minimal effect on internal validity.…”
Section: Discussionmentioning
confidence: 87%
“…). Responders were compared with nonresponders with regards to comorbidity profiles, and were found to be similar (Chaabane et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Stricter controls and more stringent regulations are being enforced in many countries towards IVF treatments in the hope of stalling the multiple pregnancy rate, however this has not been replicated in the field of ovulation induction, as this is often performed outside of large fertility clinics, or without strict tracking protocols. Hence it is believed that ovulation induction accounts for up to 65% of the world's higher order multiple pregnancies [5].…”
Section: Ovulation Inductionmentioning
confidence: 99%